Assessment of Step Tracker Mobile Applications for the Promotion of Physical Activity by Adolescents Based on Their Weight Status - Cristina M. Ponce-Ramírez; Adrián Mateo-Orcajada; Lucía Abenza-Cano; Raquel Vaquero-Cristóbal (International Journal of Telemedicine and Applications)
The objectives of the present study were to analyze the adherence of normal weight and overweight/obese adolescents to intervention with mobile applications; to establish the differences in the evaluation of the mobile application and in the problematic use of the mobile phone between normal weight and overweight/obese adolescents; and to determine the relationship between the distance travelled, the evaluation of the mobile applications, and the conflictive use of the mobile phone. A quasi-experimental design was carried out with the participation of 70 adolescents between 12 and 16 years old (mean age: 14.25±1.23 years old; 38 normal weight and 32 overweight/obese). The adolescents completed a 10-week intervention in which they used step tracker mobile applications for the promotion of physical activity, a minimum of three times per week. Problematic mobile phone use and adolescent ratings of the application used were measured. The results showed no significant differences in adolescents’ adherence to the intervention according to the mobile application used (p=0.191) or weight status (p=0.202). In addition, significant differences were not found in the assessment of mobile applications within the group of overweight and obese adolescents: engagement (p=0.471), functionality (p=0.319), aesthetics (p=0.378), information (p=0.184), usability (p=0.154), or perceived impact (p=0.139), although differences were found in the assessment made by normal-weight adolescents in information (p=0.029), usability (p=0.029), and perceived impact (p=0.044), where Pacer had better scores than Pokémon Go in the first two dimensions. No greater problematic mobile phone use was found after the intervention according to weight status (p=0.311) nor the mobile application used (p=0.985). It can be concluded that there is similar adherence among normal weight and overweight/obese adolescents to interventions with mobile applications to promote physical activity. It is noteworthy that adolescents, regardless of weight status, showed a positive perception towards the use of these mobile applications.